Literatur Review Terapi Pijat untuk Peningkatan Berat Badan pada Bayi Prematur dan atau Berat Badan Lahir Rendah (BBLR) - Dian Pratiwi (JIDAN (Jurnal Ilmiah Bidan), 2021)
Background: LBW is a valuable public health indicator of maternal health, nutrition, health service delivery, and poverty because LBW babies are at risk of death and disease immediately after birth and non-communicable diseases in the course of life. LBW is considered a significant public health problem because it is estimated that 15% to 20% of all births worldwide are LBW. Objective: to analyze the literature related to massage therapy in premature and or low birth weight infants. Methods: The method used in searching for articles is a literature review using the Google Scholar database. Results: A total of 2740 articles were identified from the database and 5 articles from manual searches. After the screening process, 13 articles were left that could be assessed for eligibility. Five of the 13 articles were excluded on grounds, leaving 8 articles for inclusion. Conclusion: Massage therapy has a positive impact on increasing the weight of LBW babies and premature babies. Keywords: Massage Therapy, Low Birth Weight Babies, Premature Babies